2003
DOI: 10.1128/mcb.23.15.5186-5197.2003
|View full text |Cite
|
Sign up to set email alerts
|

Competition between the Rad50 Complex and the Ku Heterodimer Reveals a Role for Exo1 in Processing Double-Strand Breaks but Not Telomeres

Abstract: ؉ , but the overhang reappeared following concomitant deletion of pku70 ؉ . Our data suggest that the Rad50 complex can process DSB ends and telomere ends in the presence of the Ku heterodimer. However, the Ku heterodimer inhibits processing of DSB ends and telomere ends by alternative nucleases in the absence of the Rad50-Rad32 protein complex. While we have identified Exo1 as the alternative nuclease targeting DNA break sites, the identity of the nuclease acting on the telomere ends remains elusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
160
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(175 citation statements)
references
References 69 publications
(84 reference statements)
14
160
0
1
Order By: Relevance
“…ZFNs produce 5′-cohesive ends with perfectly 4b-matched sequences, and these fragments could be employed for microhomologymediated end joining without any modification following ZFNs cleavage. Furthermore, in the case of Ku80-deficient cells, exonuclease 1 could function efficiently compared with WT cells (39). Thus, the 3′-single-strand tail produced by exonuclease 1 might also lead to the HR repair pathway for restriction enzymemediated cleavage, although this pathway is restricted to the S-to-G2 phase of the cell cycle (40).…”
Section: Discussionmentioning
confidence: 99%
“…ZFNs produce 5′-cohesive ends with perfectly 4b-matched sequences, and these fragments could be employed for microhomologymediated end joining without any modification following ZFNs cleavage. Furthermore, in the case of Ku80-deficient cells, exonuclease 1 could function efficiently compared with WT cells (39). Thus, the 3′-single-strand tail produced by exonuclease 1 might also lead to the HR repair pathway for restriction enzymemediated cleavage, although this pathway is restricted to the S-to-G2 phase of the cell cycle (40).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, Ku accumulates at HO-induced DSB sites in the absence of Mre11 (7,8) and blocks Exo1-mediated DNA resection. Deletion of Ku partially recovers DNA resection and cell survival upon IR in Mre11 mutant yeast cells suggesting the freeing of ends of Ku allows HR-mediated repair even in the absence of Mre11 (6,31). An in vitro resection assay using a long linear DNA (4.4 kb) showed that purified yKu blocked Exo1-mediated DNA resection, which could be alleviated by the addition of MRX to the reaction (7).…”
Section: Discussionmentioning
confidence: 99%
“…Myb domain-containing telomere-binding proteins have also been found in other organisms [6,7]. Fission yeast Schizosaccharomyces pombe (S. pombe) Taz1 associates with telomeric dsDNAs and plays an important role in telomere length regulation and protection [6,[8][9][10][11][12]. In addition, similar to TRF1 and TRF2, Taz1 also negatively regulates telomere length via a "protein-counting" mechanism by recruiting Rap1 and Rif1 [9,12].…”
Section: Dear Editormentioning
confidence: 99%